2005
DOI: 10.1021/la050272l
|View full text |Cite
|
Sign up to set email alerts
|

Combined Surface Pressure−Interfacial Shear Rheology Study of the Effect of pH on the Adsorption of Proteins at the Air−Water Interface

Abstract: The effect of pH on the adsorption of catalase and lysozyme at the air-water interface has been studied using a combined surface pressure-interfacial shear rheology technique. The results presented show that the rate of development of interfacial phenomena increases as the pH of the subphase approaches the isoelectric point of the protein under investigation. The development of the measured interfacial rheological parameters is due to an increased rate of cross-link formation within the resultant interfacial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 46 publications
(101 reference statements)
2
27
0
Order By: Relevance
“…Actually, more electrostatic repulsion leads to larger average distance between the adsorbed proteins, which subsequently leads to lower shear viscosity values. This was experimentally confirmed by comparing the surface shear viscosity of adsorbed layers of β-lactoglobulin [44], ovalbumin [39], and of laccase and lysozyme [6] at different pH values. It was shown that the surface shear elasticity increases when the pH of the solution is closer to pI.…”
Section: Surface Rheologymentioning
confidence: 60%
See 1 more Smart Citation
“…Actually, more electrostatic repulsion leads to larger average distance between the adsorbed proteins, which subsequently leads to lower shear viscosity values. This was experimentally confirmed by comparing the surface shear viscosity of adsorbed layers of β-lactoglobulin [44], ovalbumin [39], and of laccase and lysozyme [6] at different pH values. It was shown that the surface shear elasticity increases when the pH of the solution is closer to pI.…”
Section: Surface Rheologymentioning
confidence: 60%
“…The rate of adsorption (to a 'bare' surface) in this view depends on the interfacial unfolding of the protein. These ideas can be traced back even further in history [4], and are still applied in current literature [5][6][7]. It is important to realize that in that period of time the interactions involved in the stabilization of protein structures were still not completely understood [8].…”
Section: Protein Adsorptionmentioning
confidence: 99%
“…It is conceivable that this is due to the slightly greater 'packing' of DAMP1 compared with DAMP4 at pH 7.4, as evidenced by its slightly lower area per molecule (table 3). It has been previously observed that the lowstrain elasticity of adsorbed proteins at the air -water interface is highest around the pI [35][36][37], which is likely due to increased packing density and, therefore, 'jammed system' behaviour [1] [17], and Lac21 behaves similarly [19]. The stress response of DAMP1 reaches a plateau of 5 mN m 21 at around 10 per cent strain, at which point it is exceeded by that of DAMP4, which continues to increase to a maximum value of approximately 10 mN m 21 .…”
Section: Influence Of Molecule Length On Interfacial Rheologymentioning
confidence: 99%
“…Different effects were obtained depending on whether heating or acidification was applied before or after whey adsorption, whereas the caseins were more affected by the pre-or postadsorption pH only. Roberts et al [68] have gone further and developed a theory of interfacial aggregation and network formation as repulsion between adjacent proteins decreases as the pH approaches the pI and η i and G i increase. One might expect disulfide bond exchange to play a large role in the formation of stronger films on heating, though in fact Renault et al [69] have shown that an increase in G i for ovalbumin films may be more strongly linked to an increase in intermolecular β-sheets.…”
Section: Effects Of Cross-linking Within Protein Filmsmentioning
confidence: 99%